Variasi Joyful Learning dalam Pembelajaran Berbasis Digital Melalui IFP TV Serta Implikasinya terhadap Siswa di SD Islam Nurul Ulum Kandangan Kediri (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This research aims to: (1) identify the variations of joyful learning in digital-based instruction using Interactive Flat Panel (IFP) tvs at SD Islam Nurul Ulum Kandangan, Kediri; and (2) determine the implications of joyful learning within digital-based instruction via IFP tvs at SD Islam Nurul Ulum Kandangan, Kediri. The data for this study were derived from visual records during lessons using IFP tvs and the students of SD Islam Nurul Ulum Kandangan. This study employed a qualitative method. Ata were gathered through observation and documentation. The analysis used a descriptive qualitative technique, presenting the subjects and research findings in a narrative form. The results from several classes utilizing IFP tvs based on joyful learning revealed various engaging learning activities. These include: Student digital literature, Digital learning matches, English language learning, Fine arts stencil printing, Honesty education based on Pancasila values. These activities integrate fun, game-based learning with IFP TV technology. The digitalization of learning through IFP tvs fosters the development of students' critical thinking, agility, accuracy, and precision in their work. Additionally, students become more enthusiastic and do not experience boredom during the learning process.